Trouble in mind : an unorthodox introduction to psychiatry - MacKinnon, Dean F. (SMW productions., 2011)
Orthodox psychiatric texts are often rich in facts, but thin in concept. Depression may be defined as a dysfunction of mood, but of what use is a mood? How can anxiety be both symptom and adaptation to stress? What links the disparate disabilities of perception and reasoning in schizophrenia? Why does the same situation push one person into drink, drugs, danger, or despair and bounce harmlessly off another?